Etične dileme pri obravnavi nevroloških bolnikov v akutni bolnišnici - Hernja Rumpf, Tadeja (Rehabilitacija (Ljubljana), 2017)
Neurological diseases and their effects are a major public health problem. The disability level has been increasing because of the aging of the population. Treatment outcomes of neurological patients are better if well-organized multidisciplinary rehabilitation is provided as early as possible. We review the ethical dilemmas and the main ethical principles when providing rehabilitation to neurological patients in acute care hospital.
Keywords: early rehabilitation; ethical issues; Ethics; etični kodeks; Nervous System Diseases; neurological patients; nevrološki bolnik; rehabilitation; zgodnja rehabilitacija